ANALISA KINERJA KARYAWAN BAGIAN PRODUKSI PT. SARI MELATI KENCANA MEDAN BERDASARKAN MOTIVASI KERJA DAN DISIPLIN KERJA - Doddy Aditya; Yohny Anwar; Kiki Farida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
PT.Sari Melati Kencana Medan is a company that runs in the field F&B oriented on profit goals and strive to create competitive advantages. Employee performance is one of measuremen, which is often used in determining the effectiveness of company. A company will not able to improve if the performance of employees is stagnan, nevertheless with the high level of compotitionin the business world. In order to improve employees performance by increasing motivation of work and discipline of work. The purpose of this research is tp investigate and examine the effect of the motivation and discipline of work to employee performance of departement product PT.Sari Melati Kencana Medan. This research uses explanatory research approach of 72 respondent that taken with proportionate random sampling method. Data collection techniques is using questionnaires, interviewed, and the documentation technique. Data were analyzed using linear regression analysis. Based on the results of the analysis, it shows that motivation has positife effect toward performance about 19,6%. Employees discipline has positife effect toward performance about 17,7%. Motivation and discipline have a significant effect toward performance about 23,8%. Th higher lever of motivation and discipline of work, the higher level of performance. Advice that can be given the company is the company should be focus on laours by making some riviews of work assigments that have been established and need to be adjust between job assignment wit capability f workers. Company should give a spirirt by giving appreciation for the workers and if possible, recreation program for the works, thus eventually will improve the performance of their workers.Keywords: Motivation, Discipline Amd Performance.